Healthy migrants or health migrants? accounting for the health care utilisation patterns of Zimbabwean migrants living in South Africa - Pophiwa, Nedson (My University, 2010)
ABSTRACT Background: There is a long history of migration between Zimbabwe and South Africa. In recent years there has been a significant increase in the mix of Zimbabweans migrating to South Africa in search of better economic opportunities, fleeing political persecution, to pursue education. Little is known about the public health impact of this migration, the healthcare needs of the different categories of migrants, as well as their health-seeking strategies. The report aimed to explain the patterns of health care utilisation of Zimbabwean migrants in Johannesburg. Methods: A descriptive exploratory research design was adopted in which two methods were applied. First was the use of existing quantitative data from a recently completed survey (RENEWAL 2008) in which Zimbabwean migrants were the prominent international migrant group (n=118). Second, follow-up qualitative in-depth interviews with four respondents, were conducted to explore in detail specific cases where respondents used a public healthcare facility or where they had to make a difficult decision due to illness in a foreign country. Results: The majority of Zimbabwean migrants do not seek healthcare in South Africa neither do they report “ever falling ill” after arriving in the country. Out of 118 respondents only 25 reported an illness incidence of which 17 sought help from different health service providers, 11 of them at a government health facility. None of them was denied on the basis of their legal status. Some of the users of healthcare services, were satisfied with the treatment they received. Conclusion: There is little evidence in the findings to support the hypothesis that legal status is a deterrent factor among migrants who seek treatment at government hospitals. Instead factors such as proximity of the healthcare facility to the respondent’s place of residence were the more important reasons in choosing a certain healthcare provider. Also the generally low utilisation tendencies could be attributed to the “healthy migrant hypothesis”. A survey with a larger sample size could establish more diverse patterns of health care utilisation among Zimbabwean migrants in South Africa.